ROLE OF GRANULOCYTE COLONY-STIMULATING FACTOR (GCSF)/FILGRASTIM AS AN ADJUNCT IN CHRONIC HEPATITIS C MANAGEMENT - Fazal A. Danish; Salman S. Koul; Fazal R. Subhani; Ahmed Ehsan Rabbani; Syeda Yasmin (Journal of the Dow University of Health Sciences, 2009)
Drug-induced hematotoxicity is the commonest reason for reducing the dose or withdrawing interferon (IFN) therapy in a case o f chronic hepatitis C thus depriving the patient o f a possible cure. Traditionally, severe neutropenia has been considered an absolute contraindication to start antiviral therapy. Since the advent o f adjunct therapy with Granulocyte-colony stimulating factor, the same is not true any more. Some recent landmark studies have used this adjunct therapy to help avoid antiviral dose reductions. Although, addition o f this adjunct therapy has been shown to significantly increase the overall cost o f the treatment, if the infection is cured at the end o f the day, this extra cost is worth bearing. Although, more studies are needed to refine the true indications o f this adjunct therapy, determine the best dose regimen, quantify the average extra cost and validate that whether or not the addition o f this therapy increases the sustained virologic response rates achieved, the initial reports are encouraging. Therefore, although not recommended on routine basis, some selected patients may be given the benefits o f these factors. In this article, a review o f the current literature on this subject is given followed by few suggested recommendations at the end to help develop local guidelines.